2011
DOI: 10.1021/bi2010703
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of D1-His332 and D1-Asp170 to the Manganese Cluster of Photosystem II from Synechocystis Assessed by Multifrequency Pulse EPR Spectroscopy

Abstract: Multifrequency electron-spin echo envelope modulation (ESEEM) spectroscopy is used to ascertain the nature of the bonding interactions of various active site amino acids with the Mn ions that compose the oxygen-evolving cluster (OEC) in photosystem II (PSII) from the cyanobacterium Synechocystis sp. PCC 6803 poised in the S2 state. Spectra of natural isotopic abundance PSII (14N-PSII), uniformly 15N-labeled PSII (15N-PSII), as well as 15N-PSII containing 14N-histidine (14N-His/15N-PSII) are compared. These com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 121 publications
(386 reference statements)
11
85
0
2
Order By: Relevance
“…The parameters used (Table 1, Fig. S2, and Table S2) are similar to those reported earlier by Stich et al (31) for PSII purified from Synechocystis sp. 6803.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…The parameters used (Table 1, Fig. S2, and Table S2) are similar to those reported earlier by Stich et al (31) for PSII purified from Synechocystis sp. 6803.…”
Section: Resultssupporting
confidence: 55%
“…Instead, the observed ESEEM modulation is dominated by a 14 N hyperfine coupling assigned to the D1-His332 ligand of Mn D1 (31). At Q-band the histidine 14 N signal is at or near the cancellation condition and as such displays a maximal ESEEM response (30,31). As a consequence of the D1-His332 14 N coupling matching the cancellation condition, the signal of the bound ammonia in comparison is suppressed at Q-band and no direct information on its binding site can be obtained in this way.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…EPR spectroscopy has been used to characterize the manganese cluster (23)(24)(25)(26) extensively, and a typical, S 2 state multiline signal centered at g ϭ 2 has been well characterized. The multiline signal showed 19 -21 peaks in a range over ϳ180 mT width, and its properties have been studied by several advanced EPR techniques such as 55 Mn-ENDOR (27), ESEEM (28,29), and pulsed ELDOR (30). The ENDOR results indicated that the S 2 state is composed of one Mn(III) and three Mn(IV), where the Mn(III) ion is assigned to the Mn1 ion in the crystal structure ( Fig.…”
Section: ؉mentioning
confidence: 99%